The effects of probiotics supplementation on children with ADHD : A systematic review - Joscelind Sunaryo; Syafira Alyani; Farah J Nabila (Indonesian Nutrition Association, 2023)
ADHD (Attention deficit hyperactivity disorder) is a common neurodevelopmental disorder characterised by inattention, impulsivity and hyperactivity. Studies suggest that gut microbiota is an important player in neurological disorders including ADHD through the microbiome-gut-brain axis. The gut inflammation can negatively impact brain structures, and these inflammatory markers could influence pathogenesis of ADHD. Probiotics may be able to help the inflammation associated with increased intestinal permeability. However, clinical implementation of probiotics with ADHD is still unclear. This review examined available clinical trials related to probiotics supplementation on children with ADHD.